Stimulatory effects of activated water combined with foliar iron fertilization on photosynthetic characteristics and yield of pakchoi - Sun, Yan; Wang, Tiantian; Li, Mingyue; Wang, Yichen; Wang, Quanjiu (Frontiers in Plant Science, 2025)
The scarcity of freshwater resources, coupled with declining land productivity caused by imbalances in macro- and micronutrient ratios, severely constrains agricultural output and threatens sustainable development. At the same time, evolving dietary patterns and rising living standards have substantially increased vegetable consumption, making vegetables the second-largest crop in China after staple food crops. Therefore, this study investigated a coupled treatment system combining activated water irrigation with iron fertilization. The objectives were to conserve water resources, optimize nutrient allocation, enhance vegetable yield and quality, and provide a theoretical basis and technical support for promoting the sustainable development of the vegetable industry. Pakchoi (Brassica rapa subsp. chinensis) was selected as the experimental crop and subjected to three irrigation methods (tap water, magnetized water, and de-electronized water) under five iron fertilizer concentrations (0, 12.5, 25, 37.5, and 50 mg/L). Photosynthetic responses and yield characteristics were analyzed. Four light-response curve models (rectangular hyperbola, modified rectangular hyperbola, non-rectangular hyperbola, and exponential models) were applied to fit the photosynthetic light-response curves. Results showed that the M-Fe-1/2 treatment achieved the highest net photosynthetic rate (Pn). The maximum net photosynthetic rate (Pnmax) initially increased and then decreased with rising iron concentration, peaking at 25 mg/L. Model evaluation indicated that the modified rectangular hyperbola model provided the best fit, with the coefficient of determination (R²) closest to 1 and the lowest root mean square error (RMSE) and mean absolute error (MAE), establishing it as the optimal model for simulating light-response curves under activated water and iron co-application. Under magnetized water irrigation combined with 25 mg/L iron, model parameters—including Pnmax, apparent quantum efficiency (α), dark respiration rate (Rd), light saturation point (Isat), and light compensation point (Ic)—all reached optimal levels, while shoot fresh weight increased significantly (38.21%–100.37% higher than other treatments). These findings demonstrate that magnetized water irrigation combined with 25 mg/L iron fertilizer markedly enhances pakchoi photosynthetic capacity, activates photosynthetic metabolism, promotes assimilate accumulation, and ultimately increases yield.